Genome-Wide Identification, Evolution, and Expression Analysis of the ATP-Binding Cassette Transporter Gene Family in Brassica rapa - Yan, Chao; Duan, Weike; Lyu, Shanwu; Li, Ying; Hou, Xilin (Frontiers in Plant Science, 2017)
ATP-binding cassette (ABC) proteins can act as transporters of different substrates across biological membranes by hydrolyzing ATP. However, little information is available about ABC transporters in Brassica rapa, an important leafy vegetable. In the present study, we carried out genome-wide identification, characterization and molecular evolution analyses of ABC gene family in B. rapa and 9 other plant species. A total of 179 B. rapa ABC genes (BraABCs) were identified. Among them, 173 BraABCs were identified on 10 chromosomes. Based on phylogenetic analysis and domain organization, the BraABC family could be grouped into eight subfamilies. BraABCs in the same subfamily showed similar motif composition and exon-intron organization. Common and unique cis-elements involved in the transcriptional regulation were also identified in the promoter regions of BraABCs. Tissue-expression analysis of BraABCs demonstrated their diverse spatiotemporal expression profiles. Influences of the whole genome triplication (WGT) on the evolution of BraABCs were studied in detail. BraABCs were preferentially retained compared with their neighboring genes during diploidization after WGT. Synteny analysis identified 76 pairs of syntenic BraABC paralogs among the three subgenomes of B. rapa, and 10 paralog pairs underwent positive selection with ω (= Ka/Ks) ratios greater than 1. Analyses of the expression patterns of syntenic BraABC paralogs pairs across five tissues and under stress treatments revealed their functional conservation, sub-functionalization, neo-functionalization and pseudogenization during evolution. Our study presents a comprehensive overview of the ABC gene family in B. rapa and will be helpful for the further functional study of BraABCs in plant growth, development, and stress responses.